Recovering partial nitritation in a PN/A system during mainstream wastewater treatment by reviving AOB activity after thoroughly inhibiting AOB and NOB with free nitrous acid. (June 2020) - Wang, Bo; Wang, Zenghua; Wang, Shanyun; Qiao, Xin; Gong, Xiaofei; Gong, Qingteng; Liu, Xuefan; Peng, Yongzhen
Graphical abstract: Highlights: A strategy for recovering partial nitritation in a mainstream PN/A system is proposed. Selectively reviving AOB after thoroughly inhibiting AOB and NOB by FNA is applied. NOB reduced largely whereas AOB declined merely after 1.35 mg/L FNA treatment. Ca. Kuenenia and Ca. Brocadia formed important links with other N cycle processes. Abstract: Starting up or recovering partial nitritation is a major challenge for achieving or maintaining stable partial nitritation/anammox (PN/A) during mainstream wastewater treatment. This study presents a novel strategy for recovering the nitrite pathway by selectively reviving ammonium oxidizing bacteria (AOB) after thoroughly inhibiting AOB and nitrite oxidizing bacteria (NOB) using free nitrous acid (FNA). A sequencing batch reactor was operated for PN/A to treat real domestic wastewater for 423 days, during which twice FNA treatment was temporarily implemented. Results showed that with a single 0.45 mg/L FNA treatment on flocculent sludge, the NO3 − -N concentration during the aerobic period showed an uptrend again and the partial nitritation performance was deteriorated. In contrast, 1.35 mg/L FNA treatment induced the inhibition of both AOB and NOB leading to regressive ammonium oxidation, but a subsequently higher DO (1.5 mg/L) and longer aeration duration recovered partial nitritation. For the relative abundances of the acquired biomass related to nitrogen conversion, Nitrosomonas, Nitrospira and Nitrolancea increased to 9.65%, 10.27% and 4.35%, respectively, at the beginning of the 1.35 mg/L FNA treatment, and Nitrospira and Nitrolancea decreased to 2.80% and 0.03% whereas Nitrosomonas declined to 8.71% after 76 days. Ca. Brocadia showed less resilience after the 1.35 mg/L FNA treatment, with the relative abundance decreasing from 13.38% to 0.62% due to insufficient nitrite. Molecular ecological network analysis indicates that among anammox taxa, Ca. Kuenenia and Ca. Brocadia formed important links with other N cycle processes. Moreover, the proposed strategy shows operational flexibility because it can be easily used to control NOB in mainstream PN/A applications offered by flocculent sludge systems.